Effectiveness of External Oblique Intercostal Plane Block in Managing Acute Postoperative Pain after Laparoscopic Sleeve Gastrectomy - Aroob Zaki Khawaja, Mohsin Riaz Askri, Sahito Khan Rind, Hafiz Muhammad Waseem Yaseen, Pavan Kumar, Saeed Taj Din, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Laparoscopic sleeve gastrectomy (LSG) is a widely performed bariatric procedure that, despite being minimally invasive, results in considerable postoperative pain. Effective pain control is essential for early recovery and opioid reduction. Objective: To evaluate the impact of EOIP block on postoperative pain scores, opioid consumption, time to ambulation, and patient satisfaction in LSG patients. Methods: This prospective, randomized controlled trial was conducted at Rahbar Medical and Dental College during June 2022 to May 2023. A total of 80 adult patients scheduled for elective laparoscopic sleeve gastrectomy under general anesthesia were recruited after obtaining informed consent. Eligible participants included male and female patients aged 18 to 60 years, classified as American Society of Anesthesiologists (ASA) physical status I–III. Results: VAS scores were significantly lower in the EOIP group at all time points (p < 0.001). Mean opioid consumption over 24 hours was 6.8 ± 2.1 mg in the EOIP group versus 13.2 ± 3.4 mg in the control group (p < 0.001). The EOIP group achieved earlier ambulation (10.6 ± 3.1 hrs vs. 16.2 ± 3.8 hrs, p < 0.001) and had shorter hospital stays (2.2 ± 0.6 vs. 2.9 ± 0.8 days, p = 0.004). Patient satisfaction was higher (4.5 ± 0.6 vs. 3.7 ± 0.7, p < 0.001), and adverse events were minimal, with only one case of transient hematoma. Conclusion: It is concluded that the EOIP block significantly reduces postoperative pain and opioid requirements while enhancing early recovery and patient satisfaction after LSG. It is a safe and effective addition to multimodal analgesia strategies in bariatric surgery. Keywords: Laparoscopic, Postoperative pain, Regional anesthesia, Opioid-sparing, ERAS